THE JOURNEY OF SELF-ACCEPTANCE AND BELONGING IN NATASHA ROMANOFF’S CHARACTER IN THE MARVEL STUDIOS FILMS - Nada Ariani; Rizky Mirani Desi Pratama; Mentari Pratami (UPT Bahasa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
The purpose of this study is to examine the journey of self-acceptance (self- acceptance) and belongingness (belonging) in the character of Natasha Romanoff, which is featured in several Marvel Studios films, including Black Widow (2021), The Avengers (2012), Avengers: Age of Ultron (2015), and Avengers: Endgame (2019). This study employs qualitative research methods, including descriptive analysis, and is based on the Personality Development Theory of Elizabeth B. Hurlock (1974), with a particular emphasis on the concept of self-acceptance. The results of the analysis indicate that the character Natasha Romanoff experiences significant emotional and psychological changes. He begins his life as a traumatized individual who is subjected to the Red Room manipulation and small-scale trauma, and he gradually constructs his own identity after joining the Avengers. Natasha gradually expresses gratitude, trust, and a place to rest through her relationships with Avengers members and her family, a journey that contributes to her self-discovery. Natasha's decision to participate in the final Avengers: Endgame is the culmination of the series, during which she expresses her deepest understanding of herself and her purpose. This study demonstrates that the character Natasha Romanoff is a significant representation of the birth, death, and mourning processes in the context of social relations. It also implies that popular films can serve as a viable medium for exploring psychological and existential issues in depth